Psychiatric Comorbidity in Chronic Epilepsy: Identification, Consequences, and Treatment of Major Depression - Bruce P. Hermann; Michael Seidenberg; Brian Bell (2000)
Summary: The purpose of this article is to review the topic of interictal psychiatric comorbidity among adult patients with chronic epilepsy, focusing specifically on those studies that have used contemporary psychiatric nosology. Five specific issues are addressed: (a) the risk and predominant type(s) of psychiatric comorbidity in chronic epilepsy, (b) adequacy of recognition and treatment of psychiatric comorbidity, (c) the additional burdens that comorbid psychiatric disorders impose upon patients with chronic epilepsy, (d) the etiology of these disorders, and (e) strategies for treatment. Current appreciation for these issues in epilepsy is contrasted to related fields (e.g., primary care, psychiatry, and epidemiology), where considerable attention has been devoted to the identification, consequences, and treatment of psychiatric comorbidity. The issue of psychiatric comorbidity in epilepsy is reviewed with the aim of identifying a clinical and research agenda that will advance understanding of at least one important psychiatric condition associated with epilepsy—namely, major depression.